1981
DOI: 10.1002/jcu.1870090103
|View full text |Cite
|
Sign up to set email alerts
|

M‐mode and cross‐sectional echocardiographic diagnosis of right ventricular cavity masses

Abstract: Two patients with metastatic carcinoma (one cervical and one testicular) in whom echocardiography was instrumental in diagnosing a right ventricular cavity mass are presented. In first case the M-mode echocardiogram revealed dense echoes in the right ventricle and right ventricular outflow tract during systole and diastole. Surgical confirmation of the mass lesion was obtained. The second case also revealed abnormal echoes in the right ventricle and right ventricular outflow tract, but they were less dense and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…As for the immediate cause of death, cases in which tumor emboli of the lungs led to death have been reported, similar to our case [6, 10, 11]. If the emboli had been found and treated earlier, the symptoms could have been alleviated and the patient's prognosis could have been improved.…”
Section: Discussionsupporting
confidence: 83%
“…As for the immediate cause of death, cases in which tumor emboli of the lungs led to death have been reported, similar to our case [6, 10, 11]. If the emboli had been found and treated earlier, the symptoms could have been alleviated and the patient's prognosis could have been improved.…”
Section: Discussionsupporting
confidence: 83%
“…Electrocardiogram frequently exhibited low voltages and T-wave abnormalities in chest leads, which is indicative of myocardial disability and/or pericardial effusion ( 10 , 13 , 14 , 17 , 19 , 21 23 ). Echocardiography revealed a right ventricular mass in the majority of cases ( 1 , 6 , 10 – 12 , 14 , 16 18 , 20 24 ). In the present case, it was not obvious to suspect cardiac metastasis from the complaints of epigastric discomfort and general malaise exhibited by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English language literature revealed that only 13 well‐documented cases of right ventricular (intracavitary) metastases from cervical cancer have been described 6 –16 . The 14 cases (including the present case) are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic tumor may be totally intracavitary; usually following implants of tumor cells on the endocardium 22 . According to the literature, intracavitary mass without ventricular invasion accounts for 40% (4/10) of cases 8 –10 , 14 . The mean age of these patients is 46 years (range, 28–77 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation